Library and Information Services for National Minorities and Indigenous Peoples of Ukraine in the Context of Contemporary Challenges - Petrova, Iryna; Horb, Yevhen (Ukrainian State University of Science and Technologies, Dnipro, 2025)
ENG: The study analyses the long-term trends in library and information services for representatives of ethnic communities in Ukraine after 2014. The focus on national minority issues is due to a number of challenges faced by ethnic communities since the beginning of the hybrid aggression of the Russian Federation and the COVID-19 pandemic. During this period, regional universal scientific libraries have become a unifying hub and space for intercultural dialogue for more than 130 ethnic groups in Ukraine, some of which are on the verge of extinction or assimilation. The authors focus on the analysis of current reporting materials of library institutions, which allows us to highlight the main achievements and problematic issues in the field of ensuring the rights of minorities to library and information services. Despite the steady attention of practicing librarians to minority issues, the comprehensive processing of a significant and heterogeneous array of statistical information over the past decade has remained outside the scope of research interests of library scientists. The identified long-term trends provide a theoretical basis for a substantive, rather than declarative, solution to the problems associated with minority access to literature in their native languages.

UKR: Дослідження аналізує довгострокові тенденції, що простежуються у сфері бібліотечно-інформаційного обслуговування представників етнічних спільнот України після 2014 року. Фокус на проблематиці націнальних меншин обумовлений низкою викликів, з якими стикнулися етнічні громади з початком гібридної агресії РФ та пандемії COVID-19. Обласні універсальні наукові бібліотеки протягом окресленого періоду стали об'єднавчим хабом та простором міжкультурного діалогу для понад 130 етносів України, частина з яких знаходиться на межі зникнення, або асиміляції. Автори зосереджуються на аналізі поточних звітних матеріалів бібліотечних установ, що дає змогу виокремити основні здобутки та проблемні моменти у царині забезпечення прав меншин на бібліотечно-інформаційне обслуговування. Не дивлячись на стійку увагу практикуючих бібліотекарів до меншинної проблематики, комплексне опрацювання значного та різнорідного масиву статистичної інформації за останнє десятиліття до сьогодні залишалося поза сферою наукових інтересів вчених-бібліотекознавців. Виокремлені довгострокові тенденції дають теоретичну основу для предметного, а не декларативного вирішення проблем, пов'язаних із доступом меншин до літератури рідними мовами.
Бібліотечно-інформаційне обслуговування національних меншин та корінних народів України в умовах викликів сучасності
I. Petrova: ORCID 0000-0002-9032-3203; Ye. Horb: ORCID 0000-0002-9782-9194
Keywords: library; national minorities; indigenous peoples; library and information services; library services; бібліотека; національні меншини; корінні народи; бібліотечно-інформаційне обслуговування; бібліотечні послуги; SOCIAL SCIENCES; SOCIAL SCIENCES::Other social sciences; SOCIAL SCIENCES::Other social sciences::Library and information science